SOCIO-PSYCHOLOGICAL MECHANISMS OF IMPROVEMENT OF DECISION-MAKING IN MANAGERIAL ACTIVITIES - Nazarov Azamat Sottarovich (American Journals Publishing, 2023)
The article analyzes the scientific and theoretical features of managerial decision-making and socio-psychological factors that influence decision-making. Management decision is the main activity of a manager. Creates the direction, form and content of the work of a team of subordinates. The slightest gaps in management decisions can result in losses both for employees and, ultimately, for society.
Keywords: Personality, staff, manager, individual personality traits, making decisions, conscious choice, determinism, indeterminism.